2016
DOI: 10.33151/ajp.13.4.241
|View full text |Cite
|
Sign up to set email alerts
|

Exploring New Zealand Paramedic Attitudes towards Advance Directives: An Ethical Analysis

Abstract: IntroductionAdvance directives are known to present challenging ethical issues in health care practice, however there is a paucity of research paramedic perspectives. When a cardiac arrest occurs in the community, end of life provisions have often not been considered by patients or the patients are unable to communicate their wishes and these are not usually known to the attending paramedic crew. These factors contribute to an ethically complex decision-making environment. Ethical deliberation contribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 18 publications
0
7
0
3
Order By: Relevance
“…Seven articles investigated decision‐making in the setting of end of life. Five specifically explored decision making in out‐of‐hospital cardiac arrest (Anderson, Gott, & Slark, 2018a; Anderson, Gott, & Slark, 2018b; Bury et al, 2019; Davey, Lees, & Godbold, 2016; Davey, Lees, Misselbrook, & Godbold, 2017; Leibold, Lassen, Lindenberg, Graf, & Wiese, 2018). One was a conference abstract, two of these studies were qualitative, while the other two used a mixed‐methods approach.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seven articles investigated decision‐making in the setting of end of life. Five specifically explored decision making in out‐of‐hospital cardiac arrest (Anderson, Gott, & Slark, 2018a; Anderson, Gott, & Slark, 2018b; Bury et al, 2019; Davey, Lees, & Godbold, 2016; Davey, Lees, Misselbrook, & Godbold, 2017; Leibold, Lassen, Lindenberg, Graf, & Wiese, 2018). One was a conference abstract, two of these studies were qualitative, while the other two used a mixed‐methods approach.…”
Section: Methodsmentioning
confidence: 99%
“…It was consistent that paramedics who were uncertain on whether to resuscitate were more likely to begin resuscitation than not (Anderson et al, 2018a; Anderson et al, 2018b; Anderson, 2019). Additionally, Davey et al (2016) identified that paramedics looked to the law to help guide their decisions but noted the law did not always guide paramedics to a decision they felt was right.…”
Section: Methodsmentioning
confidence: 99%
“…This was compounded by uncertainty and lack of availability of EoL advance directives and care planning, which hindered their ability to keep patients at home. 44 57 61 65 PHPs faced a range of system-level barriers and poor EoLC coordination between services. 62 66 Informing families of death was also noted as an especially stressful, time-consuming and challenging task.…”
Section: Resultsmentioning
confidence: 99%
“…Transport home and terminal extubation by emergency medical services: an example of innovation in end-of-life care artigos contemplaram exclusivamente profissionais de saúde (Davey et al, 2016;Ferrand et al, 2006;Hoare et al, 2018;Jouffroy et al, 2017bJouffroy et al, , 2017aKamphausen et al, 2019;Lord et al, 2012;Murphy-Jones & Timmons, 2016;Patterson et al, 2019;Rogers et al, 2015;Stone et al, 2009;Waldrop et al, 2014Waldrop et al, , 2018Waldrop et al, , 2019Waldrop et al, , 2020Wiese et al, 2013;Wieseet al, 2009;Wiese et al, 2011), 13 envolveram pacientes e familiares (Burnod et al, 2012;Carron et al, 2014;Carter et al, 2019;Clemency et al, 2019;Feder et al, 2006;Jabre et al, 2008;Montgomery et al, 2017;Nemiroff et al, 2019;Swetenham et al, 2014;Taghavi et al, 2012;Wiese et al, 2008;Wieseet al, 2009;Wiese et al, 2010) e um não envolveu participantes (Guru et al, 1999).…”
Section: A33mentioning
confidence: 99%
“…Os desafios que os profissionais de saúde enfrentam durante sua atuação profissional, conforme alguns estudos demonstraram, versaram desde a falta de rastreabilidade das informações sobre o histórico de saúde do paciente, em razão da comunicação ineficiente entre os serviços de saúde (Jabre et al, 2008;Murphy-Jones & Timmons, 2016), o conhecimento e treinamento insuficiente em cuidados paliativos e cuidados a pacientes em final de vida (Waldrop et al, 2014) até a falta de documentos de manifestação dos desejos do paciente (diretivas antecipadas) (Taghavi et al, 2012) ou, na sua existência, ausência de respaldo ético, além da exigência de realizar o atendimento de forma rápida (Davey et al, 2016).…”
Section: Desafios Da Atuação Profissional No Atendimento Pré-hospitalar Em Final De Vida Por Doença Avançadaunclassified